Tworzenie wartości w ramach organizacji sieciowych - Matwiejczuk, Rafał (Value Creation within Network Organizations, 2005)
Network organization is a contemporary form of collaboration among companies which is based on cooperation processes. Value creation within network organization requires process orientation implementation. Each partner within network organization should also have indispensable resources and core competencies that determine value creation for each participant of value creation network.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 108-114